Multi‐institutional Evaluation of Radiologic Findings Associated With Pediatric Congenital Idiopathic Bilateral Vocal Fold Dysfunction. (6th October 2020) - Ruda, James; Dahl, John; McClain, Wade; Drake, Amelia; Rubel, Kolin; Onwuka, Amanda; Krakovitz, Paul; Anne, Samantha
Abstract : Objective: To report brain magnetic resonance imaging (MRI) and ultrasonography findings in pediatric patients with congenital idiopathic bilateral vocal fold dysfunction and analyze factors associated with its etiology and resolution. Study Design: Case series with retrospective review. Setting: Tertiary care multi‐institutional setting: Nationwide Children's Hospital, Indiana University, University of North Carolina, and Cleveland Clinic. Methods: Pediatric patients with congenital idiopathic bilateral vocal fold dysfunction were included in this review. Results: Congenital idiopathic bilateral vocal fold dysfunction was identified in 74 patients from 2000 to 2018. Brain MRI scans were performed in all patients and ultrasonography in 30 (40.5%). Normal imaging results were most commonly found in patients born full‐term ( P <. 0001) or via vaginal delivery ( P <. 01). Abnormal brain MRI and ultrasound results were found in 38 of 74 (51.3%) and 16 of 30 (53.3%), respectively. Type I Chiari malformation was not identified in any patient. No specific brain MRI or ultrasound abnormality was associated with patients' bilateral vocal fold dysfunction. Complete/incomplete bilateral vocal fold resolution occurred in 45 of 74 (60.8%) patients over the study interval and was not associated with brain MRI or ultrasound findings or birth complications but was associated with vaginal delivery ( P =. 02). Resolution rates were highest for patients with bilateral vocal fold paramedian paralysis ( P =. 05). Conclusions: In this multi‐institutional study, no specific brain MRI or ultrasound abnormality was associated with patients' bilateral vocal fold dysfunction or subsequent resolution rates. While imaging is often performed to detect and treat any reversible causes of bilateral vocal fold dysfunction, in this series, imaging findings were heterogeneous and did not identify any treatable causes, such as type I Chiari malformation.